Advances in the Treatment of Complex Regional Pain Syndrome: An Analysis of Current Evidence and Future Directions - Grobecki, Daniel; Korybski, Jakub; Brzozowska, Wiktoria; Jabłoński, Franciszek; Jabłońska, Hanna; Waszkiewicz, Patrycja; Lorek, Julia; Sawin, Magda; Szeliga, Katarzyna; Jarczak, Adam (Journal of Education, Health and Sport, 2026)
Background: Complex regional pain syndrome (CRPS) is a rare, multi-symptom condition characterised by severe pain that is disproportionate to the severity of the injury. Due to the lack of a standardised and fully effective treatment pathway, innovative supportive methods are being implemented in its management. Aim: The aim of this article is to summarise modern treatment methods and outline current research trends in the management of CRPS. Material and methods: A narrative review was conducted using the PICOS framework. Adult patients with CRPS type I or II were included. To focus on modern approaches, interventions for which moderate- and high-quality evidence was published after 2010 were considered, with priority given to systematic reviews and meta-analyses. Results: In neurorehabilitation, the efficacy of guided motor imagery (GMI), pain exposure therapy (PEPT) and virtual reality (VR) in reducing pain has been demonstrated. In early-phase pharmacotherapy, bisphosphonates (e.g. neridronate) demonstrate high efficacy. Ketamine infusions effectively interrupt the mechanisms of central sensitisation. In treatment-resistant patients, advanced interventional techniques are used successfully: dorsal root ganglion (DRG) stimulation, spinal cord stimulation (SCS), and repetitive transcranial magnetic stimulation (rTMS). Conclusion: Modern treatment of CRPS is based on the integration of neurorehabilitation, pharmacotherapy and precision interventional techniques. New therapeutic approaches, including targeted biological therapies and advanced neuromodulation, offer promising prospects.